2004
DOI: 10.2320/matertrans.45.3309
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Thermoelectric Properties of Hot-Pressed p-Type Bi<sub>0.5</sub>Sb<sub>1.5</sub>Te<sub>3</sub> Alloys Prepared by Rapid Solidification Technique

Abstract: Rapidly solidified bismuth-telluride based alloy foil; fabricated using the single roller melt spinning method exhibits a fine microstructure with unidirectional crystals. Meanwhile, a hot-pressing process, using rapidly solidified foils, was used to prepare the consolidated samples. The fine microstructure of this alloy is extremely effective in decreasing thermal conductivity because of the grain boundary scattering of the phonons, a key factor improving the thermoelectric properties of thermoelectric materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…The semiconductors prepared by rapid solidification exhibit considerable improvements over alloys made from conventional materials. The thermoelectric materials fabricated by rapid solidification displayed a high figure of merit [1]. Formation of dendritic structure in thermoelectric alloys impairs its thermoelectric parameters [2]- [6].…”
Section: Introductionmentioning
confidence: 99%
“…The semiconductors prepared by rapid solidification exhibit considerable improvements over alloys made from conventional materials. The thermoelectric materials fabricated by rapid solidification displayed a high figure of merit [1]. Formation of dendritic structure in thermoelectric alloys impairs its thermoelectric parameters [2]- [6].…”
Section: Introductionmentioning
confidence: 99%
“…2,3) The pulverization treatment of foils also affects the grain size, , and of the hot-pressed specimens. 2) In this study, it has become clear that the reduction of oxygen content by the heat-treatment process using hydrogen gas and the optimization of hot-pressing conditions are essential and effective means for obtaining a high figure of merit (Z).…”
Section: 3)mentioning
confidence: 99%
“…The consolidated alloy has fine microstructure with a preferential crystal orientation and exhibits a higher value of figure of merit (Z). [1][2][3] As similar for SbI 3 , HgCl 2 and HgBr 2 , oxygen has an important role in the n-type alloys for the thermoelectric properties. 4,5) However, very little is known about the influence of oxygen element on the thermoelectric properties and carrier mobility of (Bi,Sb) 2 (Te,Se) 3 alloys.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5) We proposed a new rapid solidification process for fabricating new bismuthtellurides for thermoelectric use. 6,7) The rapid solidification technique can be expected to make lower in the direction parallel to the foil thickness rather than other directions. We previously reported that, in rapidly solidified foils fabricated using the single roller method, grains are formed with the c-plane perpendicular to the surface of the cooling roller during the solidification process.…”
Section: Introductionmentioning
confidence: 99%